2018
DOI: 10.1002/brb3.922
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial DC stimulation modifies functional connectivity of large‐scale brain networks in abstinent methamphetamine users

Abstract: BackgroundTranscranial direct current stimulation (tDCS) is a noninvasive brain stimulation tool suited to alter cortical excitability and activity via the application of weak direct electrical currents. An increasing number of studies in the addiction literature suggests that tDCS modulates subjective self‐reported craving through stimulation of dorsolateral prefrontal cortex (DLPFC). The major goal of this study was to explore effects of bilateral DLPFC stimulation on resting state networks (RSNs) in associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 80 publications
(132 reference statements)
6
48
0
Order By: Relevance
“…Deficits in EFs in individuals with SUD are reflected by decreases in frontal cortex activity that interfere with decision-making, selfregulation, inhibitory control, and WM performance, which contribute to compulsive drug use and loss of control in addiction [3,54]. On the basis of previous studies [35,55] and the present results, we speculate that stimulation of the DLPFC with anodal Table 3 Results of the Mixed model ANOVAs for effects of group (active vs sham tDCS) and time (pre-intervention, post-intervention, follow-up) on executive functions and craving in patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Deficits in EFs in individuals with SUD are reflected by decreases in frontal cortex activity that interfere with decision-making, selfregulation, inhibitory control, and WM performance, which contribute to compulsive drug use and loss of control in addiction [3,54]. On the basis of previous studies [35,55] and the present results, we speculate that stimulation of the DLPFC with anodal Table 3 Results of the Mixed model ANOVAs for effects of group (active vs sham tDCS) and time (pre-intervention, post-intervention, follow-up) on executive functions and craving in patients.…”
Section: Discussionmentioning
confidence: 96%
“…In methamphetamine-use disorder, which is the focus of the present study, recent evidence from neuroimaging studies have shown that tDCS applied bilaterally over the DLPFC increases functional connectivity of the resting-state executive control network [35]. Other tDCS studies in methamphetamine-use disorder showed that anodal right, left or bilateral DLPFC stimulation reduced drug cue-induced craving and attentional bias [30,31,35], and a case study reported improved effects of multiple tDCS sessions on both craving and cognitive impairment [36]. These studies, except for the latter case report, only examined the impact of tDCS on craving, but not other clinical parameters, and also did not systematically explore the effects of repeated tDCS over the DLPFC on executive dysfunctions in methamphetamine-use disorder.…”
Section: Introductionmentioning
confidence: 88%
“…The induced craving was measured with fMRI and subjective reports (i.e., self‐reported visual analogue scale pre‐ and post‐imaging). Anode and cathode electrodes were placed over left and right dorsolateral prefrontal cortex (DLPFC) (F3,F4 based on 10–20 EEG system) and 2 mA direct current for 20 min was administered during active stimulation session (Shahbabaie et al, ).…”
Section: Tdcs‐mr Imaging: Trial Design Parameter Spacementioning
confidence: 99%
“…Long-lasting effects of tDCS share some similarities with long-term potentiation and depression (LTP and LTD) of glutamatergic synapses, as suggested by pharmacological studies in both, animals ( Rohan et al, 2015 ) and humans ( Liebetanz et al, 2002 ; Nitsche et al, 2003a , 2004 ). Although the method is still experimental, preliminary findings suggest that tDCS might be a potential clinical treatment for drug addiction ( Feil and Zangen, 2010 ; Yavari et al, 2015 ), such as nicotine ( Fregni et al, 2008 ; Boggio et al, 2010 ; Fecteau et al, 2014 ; Meng et al, 2014 ), alcohol ( Boggio et al, 2008 ; Nakamura-Palacios et al, 2012 ; da Silva et al, 2013 ; Klauss et al, 2014 ), cocaine ( Conti and Nakamura-Palacios, 2014 ; Conti et al, 2014 ; Gorini et al, 2014 ), marijuana ( Boggio et al, 2010 ), heroin ( Wang et al, 2016 ), and methamphetamine dependency ( Shahbabaie et al, 2014 , 2018 ). Although these studies have reported promising therapeutic effects, electrode montages differ between studies, and it has not been sufficiently explored which montage results in optimal effects.…”
Section: Introductionmentioning
confidence: 99%